2017
DOI: 10.1155/2017/8424628
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anemia in Pediatric IBD Patients and Impact on Disease Severity: Results of the Pediatric IBD-Registry CEDATA-GPGE®

Abstract: Aim To determine the prevalence of anemia and its association with disease severity in children and adolescents with IBD. Methods CEDATA-GPGE is a registry for pediatric patients with IBD in Germany and Austria from 90 specialized centers. As markers of disease severity, analysis included patient self-assessment on a Likert scale (1–5; 1 = very good) and physicians' general assessment (0 = no activity to 4 = severe disease) and the disease indices. Anemia was defined as hemoglobin concentration below the 3rd p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Reduced muscle mass[20] and anemia[21-23], both of which are frequently observed in patients with IBD, even when their disease is in remission, may also have affect fatigue, but so far, these factors have not been investigated in the adolescent IBD population.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced muscle mass[20] and anemia[21-23], both of which are frequently observed in patients with IBD, even when their disease is in remission, may also have affect fatigue, but so far, these factors have not been investigated in the adolescent IBD population.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to corticosteroid treatment and a low weight-for-age, our study identified anemia as a potential risk factor of B2 behavior, which has not been reported yet. Nevertheless, previous studies associated anemia with higher disease activity as well as lower self-assessed well-being supporting an impact of anemia on the development of a B2 behavior ( 24 ). Our study identified emesis as a risk factor and diarrhea as a protective factor of B2 behavior, which has not been reported yet.…”
Section: Discussionmentioning
confidence: 91%
“…The existing research in the pediatric population provides contradictory results regarding the prevalence of anemia among the different types of IBD. Previous studies found an association between disease type and prevalence of anemia, reporting a higher frequency in patients with CD than in patients with UC [16,19,20]. A possible explanation of this difference is that, in CD patients, more pathogenic mechanisms may play a role in the development of anemia, such as systemic inflammation, which is usually more severe in CD than in UC, Vitamin B12 malabsorption due to the terminal ileum involvement, and iron malabsorption due to the proximal gastrointestinal tract involvement.…”
Section: Discussionmentioning
confidence: 96%